An Update on the Fall Armyworm: Severity of Maize Damage and Susceptibility to Emamectine Benzoate and Chlorantraniliprole - Trisyono, Y. Andi; Hendrayanti, Hadvina Nur; Yuantomoputro, Arzaq P.; Setyaningrum, Ary V.; Harjanto, Sriyanto; Aryuwandari, Valentina E. F. (Jurnal Perlindungan Tanaman Indonesia, 2024)
The damage area due to fall armyworm (FAW, Spodoptera frugiperda) in Indonesia decreased during the last three years (2021-2023) after the first outbreak in 2019. This insect continues to pose some risk for maize production with most reports documented the damage during the vegetative maize stage showing leave defoliation. This article provides an update on the high field population and the new type of damages caused by FAW by boring the stalks and feeding the cobs observed in the District of Grobogan, Central Java. The populations of egg masses, adults, and larvae were 0.4, 0.17, and 0.37 per plant of 27-day-old, respectively. The reproductive maize was heavily damaged by FAW with leave damage score of 9, 0.33 holes per stalk, and 75% of cobs damaged. The FAW larvae produced from the collected egg masses were still susceptible to emamectin benzoate and chlorantraniliprole. These findings prove that FAW can cause very serious damage leading to almost total yield loss. As maize becomes more important in Indonesia, proper management in compliance with the Integrated Pest Management (IPM) principles is mandatory to keep the population low and prevent large-scale outbreaks.